Complete sequence and characterization of mitochondrial genome of Jianyang Daer goat (Capra hircus). (3rd May 2016) - Hu, Jiangtao; Zhong, Tao; Wang, Linjie; Li, Li; Fan, Jingsheng; Xiong, Chaorui; Wang, Yong; Zhang, Hongping
Abstract: This study has presented the complete mitogenome of Jianyang Daer goat ( Capra hircus ), a crossbreed known for its high growth rate and good-meat quality in China. The mitogenome was 16, 643 bp in length, including 33.54% A, 26.07% C, 13.10% G and 27.29% T. It contained a non-coding control region, 2 ribosomal RNA genes, 13 protein-coding genes and 22 transfer RNA genes. Two kinds of inititiation codon and four types of termination codon were identified. Moreover, most of the genes were encoded on H-strand. These information will be useful for further investigation on the genetic divergence among Chinese domestic goats.